2021
DOI: 10.3389/fimmu.2021.767000
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Mapping of HBsAg Loss-Related B-Cell Linear Epitopes in Chronic HBV Patients by Peptide Array

Abstract: Identification of immunogenic targets against hepatitis B virus (HBV)-encoded proteins will provide crucial advances in developing potential antibody therapies. In this study, 63 treatment-naïve patients with chronic HBV infection and 46 patients who achieved hepatitis B surface antigen loss (sAg loss) following antiviral treatment were recruited. Moreover, six patients who transitioned from the hepatitis B e antigen-positive chronic infection phase (eAg+CInf) to the hepatitis phase (eAg+CHep) were enrolled fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The increasing epitopes occupancy could forecast enhanced antibodies neutralization and functional cure in patients with chronic HBV infection after nucleos(t)ide analog treatment 29 . In addition, our previous study also identified several functional cure‐related B‐cell linear epitopes, which were different from the candidate epitope S29 in our study 30 . The seemingly paradox may result from discrepant immunological mechanism of vaccine and natural HBV infection.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The increasing epitopes occupancy could forecast enhanced antibodies neutralization and functional cure in patients with chronic HBV infection after nucleos(t)ide analog treatment 29 . In addition, our previous study also identified several functional cure‐related B‐cell linear epitopes, which were different from the candidate epitope S29 in our study 30 . The seemingly paradox may result from discrepant immunological mechanism of vaccine and natural HBV infection.…”
Section: Discussionmentioning
confidence: 55%
“…29 In addition, our previous study also identified several functional cure-related B-cell linear epitopes, which were different from the candidate epitope S29 in our study. 30 The seemingly paradox may result from discrepant immunological mechanism of vaccine and natural HBV infection. On all accounts, both studies strengthened the necessity of "a determinant region" in inducing neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant B cell epitopes (S76 and S78) in patients with negative HBsAg may be significant candidates for treatment to achieve a functional cure. 49 During PegIFNα treatment, the proportion of total B cells and plasma B cells in the HBsAg-negative group was higher than that in the HBsAgpositive group, when other factors including age, sex, and treatment duration were completely matched. 50…”
Section: Effect Of Continuous Hbsag Seroclearance On Immune Functionmentioning
confidence: 90%
“…It is progressively recognized that B cells play an extremely important role in the continuous control of HBV, and the generation of HBsAb is not only a mark of acute infection resolution but also the ultimate goal of the functional cure of CHB 57 . HBsAg‐specific B cells persist in the blood and liver of many patients with CHB, however, these cells are substantially defective in antibody production, which was consistent with undetectable levels of anti‐HB antibodies in vivo 58 . The dysfunctional HBsAg‐specific and global B cells cluster CD21/CD27 atypical memory B cells (ATM‐Bs) with high expression of inhibitory receptors (including PD‐1); in turn, blocking PD‐1 could partially restore B‐cell function and increases antibody generation 59 .…”
Section: Strategies To Control Hbv Infection Based On Immunological M...mentioning
confidence: 99%
“…57 HBsAg-specific B cells persist in the blood and liver of many patients with CHB, however, these cells are substantially defective in antibody production, which was consistent with undetectable levels of anti-HB antibodies in vivo. 58 The dysfunctional HBsAg-specific and global B cells cluster CD21/CD27 atypical memory B cells (ATM-Bs) with high expression of inhibitory receptors (including PD-1); in turn, blocking PD-1 could partially restore B-cell function and increases antibody generation. 59 Importantly, longitudinal observation showed that ATM-B cells were related to the successful treatment of CHB.…”
Section: S Tr Ateg Ie S To Control Hbv Infec Tion Ba S Ed On Immunolo...mentioning
confidence: 99%